نموذج رياضي لتقدير التبخر اليومي في المنطقة السهلية في الساحل السوري باستخدام برمجة التعبير الجيني - غطفان عمار; منذر حماد; ماريا عباس (Tishreen University, 2019)
The evaporation is one of the basic components of the hydrologic cycle. It is necessary to estimate accurately it for the development and management of water resources, it affects the amount of runoff, the capacity of surface reservoirs, and the plant's need for water, and it requires knowledge of many climatic variables. Although, there are many empirical formulas available for estimation of evaporation, but their performances are not all satisfactory due to the complicated nature of the evaporation process. Therefore, this research aims to develop a mathematical model to estimate the daily evaporation in the Syrian coast of plateau using available climatic data, taken from five climatic stations distributed over the entire studied area and located at different altitudes. For this the model was built using gene expression programming. Different models were evaluated according to the model inputs. The statistical parameters used to evaluate the accuracy of the proposed model were: Root Mean Squared Error (RMSE) and correlation coefficient (R). The study showed that the model including temperature, relative humidity, solar radiation and elevation is the best for estimating daily evaporation in the Syrian coast. The RMSE and R values ​​were respectively (0.525mm/day) and (0.944). The study recommends expanding the use of gene expression programming in hydrological studies, and compares with artificial intelligence methods. يعتبر التبخر مكوناً رئيسياً للدورة الهيدرولوجية، ومن الضروري تقديره بدقة من أجل تنمية وإدارة الموارد المائية، فهو يؤثر على كمية الجريان، وحجم التخزين السطحي، وعلى الاحتياج المائي للنبات. ويتطلب تقديره معرفة العديد من العناصر المناخية. على الرغم من أن هناك صيغاً تجريبيّة متوفرة لتقدير التبخر، لكن بعض هذه الطرائق صالحة فقط في ظروف مناخية محددة ولا يمكن تطبيقها في ظروف مختلفة. لذلك فإن هذا البحث يهدف لوضع نموذج رياضي لتقدير التبخر اليومي في المنطقة السهلية في الساحل السوري باستخدام بيانات مناخية متوفرة، أخذت من خمس محطات مناخية موزعة على كامل مساحة المنطقة المدروسة ومتوضعة على ارتفاعات مختلفة. من أجل ذلك فقد بني النموذج باستخدام برمجة التعبير الجيني. وتم تقييم نماذج مختلفة باختلاف مدخلات النموذج. وكانت المعايير الإحصائية المستخدمة لتقييم دقة النموذج المقترح هي: جذر متوسط مربع الخطأ (RMSE) ومعامل الارتباط ( )، وقد بينت الدراسة أن النموذج المتضمن درجة الحرارة والرطوبة النسبية والإشعاع الشمسي والارتفاع، هو الأفضل لتقدير التبخر اليومي المنطقة السهلية في الساحل السوري، حيث كانت قيمة (RMSE=0.525mm/day) وقيمة . توصي الدراسة بالتوسع في استخدام برمجة التعبير الجيني في الدراسات الهيدرولوجية، ومقارنتها مع طرائق الذكاء الاصطناعي المختلفة.